Inventarisasi Teritip Non-Indigenous yang Menempel pada Ocean Going Vessel di Pelabuhan Tanjung Intan Cilacap - Romanus Edy Prabowo; Erwin Riyanto Ardli (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Portof Tanjung Intan Cilacapis one of four major international shipping ports located in JawaIslandand among 85 ports throughout Indonesia. International shipping ports are exposed for non-indigenous species including barnalces as a consequence of shipping traffic. Barnacle is the most common marine fouling found in ship’s hull and ballast water of ocean going vessel. This work was aimed at knowing which barnacle species were passively transported on such vessels hulls, in order to map and monitor non-indigenous species invasion in the area. Four vessels of different origins were investigated between April and November 2009. Among four vessels, three of them were clean. A cosmopolite non-invasive species were found on a ship of Ukrainan origin, Amphibalanus amphitrite., which also occur dominantly in the port of Tanjung Intan Cilacap. This port was considered at no introduction risk of non-indigenous species.